Integration of Artificial Intelligence into Creative Writing Learning Models: A Literature Review of Approaches and Effectiveness - Marwani; Ribut Wahyu Eriyanti; Hari Sunaryo (International Journal of Community Engagement Payungi, 2025)
Technological advancements in the Society 5.0 era have driven the integration of artificial intelligence (AI) into various aspects of education, including creative writing learning. AI functions as a tool to assist students in generating ideas, structuring their writing, and receiving adaptive feedback. However, the implementation of AI in writing education still faces several challenges, such as the potential for grammatical inaccuracies, limited emotional depth, and a tendency to generate overly simplistic texts. This study aims to review various AI-based learning approaches and improve their effectiveness in developing the creative writing skills of students. A Systematic Literature Review (SLR) method and using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines was employed by analyzing previous studies related to the integration of AI in creative writing education. The findings of this study indicate that the ChatGPT platform is widely utilized in the development of creative writing, particularly short stories.  ChatGPT has proven effective in enhancing the writing skills of students by facilitating idea generation and supporting information exploration. Moreover, AI proves most effective when used as a collaborative tool within pedagogically grounded models, rather than as a replacement for human creativity. This study contributes to the enhancement of student creative writing skills by mapping current AI developments, identifying the most effective instructional models, and providing evidence-based recommendations for integrating AI to improve student performance in creative writing education.